Long Term Health Effect of Earned Income Tax Credit - Ze Song (Rutgers University, Department of Economics, 2019)
Using decades of variation in the federal and state Earned Income Tax Credit (EITC) and the Panel Study of Income Dynamics (PSID) dataset, I examine the impact of exposure to EITC expansions in utero and during childhood on health outcomes in adulthood. In order to overcome the confounding relationship between family income and health outcomes, this study uses the maximum EITC benefit as the key variable. Reduced-form estimates show that EITC expansions had a positive impact on self-reported health status. Specifically, a 1000 increase in the maximum EITC exposure from ages 13 to 18 corresponds with a 0.01 point increase in the reported health status during adulthood. In addition, being exposed to EITC expansions in utero increases reported health status by 0.05 point. Relative to the range of reported health of 1 to 5 and the standard deviation of 0.94, these are very small effects. Nonetheless, these health effects are consequential, associating with increases in both family income and maternal labor supply.
Keywords: I1; H2; 330; EITC; health effect